Perbedaan Manajemen Konflik pada Organisasi Kemahasiswaan Bem Fikes dan Bem Feishum di Universitas ‘Aisyiyah Yogyakarta - Ades Adelia Puspitasari; Mustaqim Setyo Ariyanto; Annisa Warastri (Jurnal Syntax Admiration, 2024)
Abstract This study aims to identify the differences in conflict management between BEM FIKES and BEM FEISHUM of 'Aisyiyah University Yogyakarta. This study uses a quantitative approach with a comparative design, data was obtained through a questionnaire involving 110 respondents consisting of BEM FIKES and BEM FEISHUM administrators. The results of the analysis based on the Independent Sample t-Test showed that BEM FIKES obtained a higher score of 65.98 compared to BEM FEISHUM of 62.68 with a significance value (p) of 0.003. This difference indicates the influence of conflict management strategies on the effectiveness of conflict resolution between the two organizations. BEM FIKES tends to use an avoidance approach and relies on the role of the leader while BEM FEISHUM uses a collaborative approach and tends to be open to discussion. This research is expected to be a reference for student organization administrators to understand the importance of conflict management in improving organizational skills.